Mannerheim : president, soldier, spy - Clements, Jonathan, 1971- (London : Haus Publishing, 2012)
""An exemplary and generously illustrated account; it incorporates new historical material, and he describes the journey as if he had been there.""--The Times Literary Supplement Gustaf Mannerheim was one of the greatest figures of the twentieth century. He spent two years undercover in Asia as a spy, escaped the Bolsheviks in 1917, lead the anti-Russian forces in the civil war and later, during Finland's darkest hour, lead the defense of his country against the impossible odds of the Winter War. Mannerheim is a fascinating appraisal of an adventurer and explorer who would go on to forge a ne.
Title Page; Contents; Note on Dates; Introduction: Cold Mountain; 1. Mannerheim's World; 2. The Field of Vipers; 3. The Baptism of Fire; 4. The Tournament of Shadows; 5. The Horse Reaches China; 6. The Paper Dragons; 7. The End of Empire; 8. The White Devil; 9. The House of the Four Winds; 10. The Jaws of Peril; 11. The Eye of the Storm; 12. Marski; Afterword: Mannerheim in the 21st Century; Notes on Names; Notes; Sources and Further Reading; Acknowledgements.
Online resource; title from PDF title page (EBSCO, viewed July 7, 2016).
Includes bibliographical references.
JSTOR
Keywords: Mannerheim, Carl Gustaf Emil, -- 1867-1951.; Mannerheim, Carl Gustaf Emil, -- 1867-1951; Soldiers -- Finland -- Biography; Presidents -- Finland -- Biography; Russo-Japanese War, 1904-1905.; Russo-Finnish War, 1939-1940.; Finland -- History -- 20th century; Présidents -- Finlande -- Biographies; Guerre russo-japonaise, 1904-1905.; Guerre soviéto-finlandaise, 1939-1940.; Finlande -- Histoire -- 20e siècle.; HISTORY -- Europe -- Scandinavia; BIOGRAPHY & AUTOBIOGRAPHY -- General; Presidents; Soldiers; Finland; 1900-1999; Biographies; History